2015
DOI: 10.1002/qre.1896
|View full text |Cite
|
Sign up to set email alerts
|

EWMA Control Chart Performance with Estimated Parameters under Non-normality

Abstract: Exponentially weighted moving average (EWMA) control charts can be designed to detect shifts in the underlying process parameters quickly while enjoying robustness to non‐normality. Past studies have shown that performance of various EWMA control charts can be adversely affected when parameters are estimated or observations do not follow a normal distribution. To the best of our knowledge, simultaneous effect of parameter estimation and non‐normality has not been studied so far. In this paper, a Markov chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…This implies that non-normality and contaminated data are a major concern when one deals with geometric profiles. As stated in the studies conducted by Borror et al 14 and Noorossana et al, 15,16 t and Gamma distributions provide decent grounds to investigate the effect of non-normality in different applications of SPC. Similar to normal distribution, the t distribution is symmetric around mean but with heavier tails probabilities.…”
Section: Non-normalitymentioning
confidence: 99%
“…This implies that non-normality and contaminated data are a major concern when one deals with geometric profiles. As stated in the studies conducted by Borror et al 14 and Noorossana et al, 15,16 t and Gamma distributions provide decent grounds to investigate the effect of non-normality in different applications of SPC. Similar to normal distribution, the t distribution is symmetric around mean but with heavier tails probabilities.…”
Section: Non-normalitymentioning
confidence: 99%
“…where ARL is calculated by (28). Since the integrals in (24), (25), and (28) are difficult to compute directly, the Gauss-Legendre quadrature (see [47], [48]) is used to obtain an approximation of the integrals.…”
Section: The Run Length Properties Of One-sided Exponential Ewma Chmentioning
confidence: 99%
“…For the lower-sided exponential EWMA chart, [30] showed that RL distributions are generally right skewed, and the shape of the RL distribution is uncertain due to the effect of parameter estimation. In order to assess the interpretation of ARL, the percentiles of the RL distribution and the ARL are calculated for the lower-sided exponential EWMA chart by using (26) and (28) in Section II. In addition, F ARL is also calculated by using (29) to visualize the meaning of the ARL.…”
Section: Interpretation Problems Of the Arl-based Exponential Ewmamentioning
confidence: 99%
“…They were also able to use the bootstrap method in multivariate control charts for principal component analysis based on non-normal distributions when subgroup size is one (Phaladiganon, Kim, Chen, & Jiang, 2013). Mostajeran, Iranpanah, and Noorossana (2016) proposed a new bootstrap algorithm to construct Hotelling's T 2 control chart for individual observations (n = 1).…”
Section: Introductionmentioning
confidence: 99%